2000 years of North Atlantic-Arctic climate. (15th July 2019) - Auger, Jeffrey D.; Mayewski, Paul A.; Maasch, Kirk A.; Schuenemann, Keah C.; Carleton, Andrew M.; Birkel, Sean D.; Saros, Jasmine E.
Abstract: The North Atlantic-Arctic boundary is highly variable due to the transports of heat and moisture through the Gulf Stream and polar jet stream. The North Atlantic storm track generally follows the Gulf Stream and terminates near southeast Greenland and Iceland as the Icelandic Low. The Icelandic Low is the main driver of the North Atlantic Oscillation, particularly during winter months as the baroclinic zone expands to lower latitudes, correlating with temperature and precipitation in many areas around the North Atlantic. Understanding how atmospheric circulation, temperature, and precipitation changes in this region is important to build robust projections of how these variables will change, especially under natural and anthropogenic forcings. Here, climate proxies correlating to the Icelandic Low, summer air temperature, and annual precipitation build an understanding of how these variables changed over the last 2000 years. Through the natural climate shifts of this period — Roman Warm Period, Dark Ages Cold Period, Medieval Climate Anomaly, and Little Ice Age — it is shown that storm frequency decreases as temperature increases and the Icelandic Low increases in pressure (i.e., becomes weaker). However, these climate changes are not simultaneous, and their amplitudes are not similar across the region. Keeping regionality rather than a pan-Arctic average better explains natural variability of each sub-region and how each sub-region has evolved climatically due to anthropogenic forcings of greenhouse gases.